A PORTRAIT OF SELFSECURE WOMEN AMIDST INSECURITIES IN PREETHI NAIR’S ONE HUNDRED SHADES OF WHITE - Vennila; Ruby, M Angeline (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian women writers of twentieth century mainly spot light on casteism, silent suffering women who become the victims of the atrocities of dominant men, child marriage and constrained widowhood. Indeed the scenerio has been changed in the contemporary century where the focus is on women who start questioning the traditional patriarchal norms and search for their self idendity. It is quite true in the case of Preethi Nair who depicts women rising as phoenix from the ashes of victimisation. The women characters of Nair’s One Hundred Shades of White though abandoned by their husbands, rejected, betrayed by their beloveds, put in an alien world where cultural conflicts arise, threatened by the harsh realities of life and no matter what, but rise to the occasion to prove themselves. They are exhibits of empowered women who are selfsecure amidst insecurities and so leading a dignified living.